1992
DOI: 10.1007/bf02333019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking and of a transdermal nicotine delivery system on glucoregulation in type 2 diabetes mellitus

Abstract: The effect of nicotine absorbed transdermally from a patch (TNS) and from cigarette smoking on insulin secretion and action in Type 2 diabetes has been compared. Twelve Type 2 diabetic smoking patients, aged 51 y, with diabetes for 9 y, treated either with diet and/or oral hypoglycaemic agents, were studied on three occasions, according to a double-blind, placebo-controlled, cross-over design. The subjects were investigated 12 h after their last cigarette or application of one patch of TNS 30 cm2 or TNS placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…For diabetes, several human studies demonstrate nicotine exposure results in enhanced insulin resistance in type 2 diabetics but not in healthy individuals (Axelsson et al 2001; Epifano et al 1992). For example, a study from Axelsson and co-workers investigated the effects of acute intravenous nicotine infusion on insulin sensitivity in non-smoker type 2 diabetics versus healthy non-smoker controls.…”
Section: Resultsmentioning
confidence: 99%
“…For diabetes, several human studies demonstrate nicotine exposure results in enhanced insulin resistance in type 2 diabetics but not in healthy individuals (Axelsson et al 2001; Epifano et al 1992). For example, a study from Axelsson and co-workers investigated the effects of acute intravenous nicotine infusion on insulin sensitivity in non-smoker type 2 diabetics versus healthy non-smoker controls.…”
Section: Resultsmentioning
confidence: 99%
“…There is some evidence that cigarette smoking could acutely impair insulin action in normal subjects and T2DM patients (31, 32) and clinical studies have shown that direct negative effects of smoking on β-cells (21). Similarly, this study revealed that daily cigarette consumption was positively associated with insulin secretion and the latter was negatively related to T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…This acute effect could be mediated by a stimulation of the sympathetic nervous system by nicotine, leading to enhanced catecholamine levels and insulin resistance. Indeed, long-term use of nicotine-containing chewing gum has been associated with insulin resistance (26), and some studies indicate that acute administration of nicotine induces insulin resistance (27). However, transient acute smoking does not appear to affect insulin secretion (27), and the long-term effects of tobacco use on insulin secretion remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, long-term use of nicotine-containing chewing gum has been associated with insulin resistance (26), and some studies indicate that acute administration of nicotine induces insulin resistance (27). However, transient acute smoking does not appear to affect insulin secretion (27), and the long-term effects of tobacco use on insulin secretion remain unclear. In the Stockholm Diabetes Prevention study (28), a cross-sectional study of 3,129 middle-aged Swedish men, the risk of diabetes was increased in current smokers compared with former smokers.…”
Section: Discussionmentioning
confidence: 99%